2015
DOI: 10.5194/npg-22-349-2015
|View full text |Cite
|
Sign up to set email alerts
|

Stress states and moment rates of a two-asperity fault in the presence of viscoelastic relaxation

Abstract: Abstract.A fault containing two asperities with different strengths is considered. The fault is embedded in a shear zone subject to a constant strain rate by the motions of adjacent tectonic plates. The fault is modelled as a discrete dynamical system where the average values of stress, friction and slip on each asperity are considered. The state of the fault is described by three variables: the slip deficits of the asperities and the viscoelastic deformation. The system has four dynamic modes, for which analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Belardinelli and Bonafede (1995) modelled afterslip as driven by viscous flow in the asthenosphere. A study of the effects of viscoelastic relaxation on a complex fault was made by Amendola and Dragoni (2013) and Dragoni and Lorenzano (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Belardinelli and Bonafede (1995) modelled afterslip as driven by viscous flow in the asthenosphere. A study of the effects of viscoelastic relaxation on a complex fault was made by Amendola and Dragoni (2013) and Dragoni and Lorenzano (2015).…”
Section: Introductionmentioning
confidence: 99%
“…We assume that coseismic stresses are relaxed with a characteristic Maxwell time Θ, as a consequence of viscoelastic relaxation in the asthenosphere following an earthquake on the fault. Following Dragoni and Lorenzano (2015), all quantities are expressed in nondimensional form.…”
Section: The Modelmentioning
confidence: 99%
“…In these works, the fault was treated as a discrete dynamical system characterized by three slipping modes, corresponding to the failure of one or both asperities at a time. Dragoni and Lorenzano (2015) considered a fault with two asperities of different strengths in the presence of viscoelastic relaxation. The authors showed that the knowledge of the state of the system at a given instant in time allows to calculate its orbit in the phase space and to predict its subsequent evolution, in the absence of stress perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscoelastic relaxation of lithospheric rocks may change the stress distribution in the long term as a consequence of larger earthquakes (e.g. Dragoni and Lorenzano, 2015).…”
Section: The Modelmentioning
confidence: 99%